AFFECTIVE THEORY ACCORDING TO EXPERTS: TEORI AFEKTIF MENURUT PARA AHLI - rahmatia inaku; Iwan B. Jassin (LPPM UNiversitas Bina Mandiri Gorontalo, 2022)
This journal presents a comprehensive review of affective theory according to experts. Affect refers to the emotional aspects, feelings, and moods of individuals. This article is presented using qualitative methods. Understanding and analyzing affective theory can provide valuable insights in understanding human behavior, social interaction, and decision making. In this journal, we collect different views and approaches from leading experts in this field. Analysis and comparison between these theories provides a better understanding of the concept of affective and its influence in various contexts. It can be concluded that affective (attitude) is a person's tendency to accept or reject awareness that is considered good or bad, by bringing up a positive attitude or a negative attitude. This attitude has an important role in taking action and finding various alternatives. Affective is also closely related to emotions, feelings, values, appreciation, motivation, and attitudes. This deep understanding of the influence of affect on human behavior and experience has relevant implications in many areas of life, including education, marketing, and emotion management.